Chemotherapy nurses’ experience: A phenomenology study - Hubjaroen, Sakorn; Matchim, Yaowarat (Journal of Research in Nursing-Midwifery and Health Sciences, 2016)
This study aimed to describe experience of chemotherapy nurses working at chemotherapy clinic, Songklanagarind Hospital. Data were collected by using individual in-depth interview with 8 chemotherapy nurses. The framework of van Manen’s lifeworld existentials of lived body, lived relation, lived space and lived time-guided reflection for data analysis. Trustworthiness was established following the criteria set by Lincoln and Guba. The findings show essential themes situated in the context of the four existential ground of body, relation, space, and time emerged. These themes were: 1) being proud of oneself; 2) feeling not being accepted and understood by nurses in other units; 3) being locked in a small poisonous box; and 4) having time for learning the reality of life, respectively. The findings of this study help to understand the experience of chemotherapy nurses working at chemotherapy clinic, Songklanagarind Hospital. In addition, the findings can be used as database for managing and developing this chemotherapy clinic for more effective and safe.